Another World : Mito Annual '93. (Mito : Art Tower Mito - Contemporary Art Gallery, 1992)
Kapoor, Anish ; Hokusai, Katsushika ; Rothko, Mark ; Fabre, Jan ; Wilson, Richard ; Dumb Type ; Clemente, Francesco
2 vol.: Another World : Mito Annual '93, 130 p. : ill. + Another World : Mito Annual '93 : Document of the Exhibition, 57 p. : ill.
Another World : Mito Annual '93, Art Tower Mito - Contemporary Art Gallery, Mito, 21st November 1992 - 7th March 1993
boek